Effects of magnesium picolinate, zinc picolinate, and selenomethionine co-supplementation on reproductive hormones, and glucose and lipid metabolism-related protein expressions in male rats fed a high-fat diet - Şahin, Kazım; Orhan, Cemal; Küçük, Ömersman; Tuzcu, Mehmet; Şahin, Nurhan; Ozercan, Ibrahim H.; Komorowski, James R. (Elsevier, 2022)
This study aimed to examine the impacts of the magnesium picolinate (MgPic), zinc picolinate (ZnPic), and selenomethionine (SeMet) alone or as a combination on blood metabolites, oxidative enzymes, reproductive hormones, and glucose and lipid metabolism-related protein expressions in Wistar rats fed a high-fed diet (HFD). The rats were fed either a control, HFD, or HFD supplemented with a single (MgPic, ZnPic, SeMet) or two or three organic mineral combinations. Body weights, visceral fat, serum glucose, insulin, total cholesterol, triglycerides, leptin, malondialdehyde (MDA) concentrations as well as liver sterol regulatory element-binding protein-1c (SREBP-1c), liver X receptor alpha (LXR alpha), ATP citrate lyase (ACLY), fatty acid synthase (FAS), and nuclear factor kappa B (NF-kappa B) levels increased, while serum testosterone, follicle-stimulating hormone (FSH), luteinizing hormone (LH), sex hormone-binding globulin (SHBG), and insulin-like growth factor (IGF-1) concentrations along with liver nuclear factor erythroid 2-related factor 2 (Nrf2) levels declined in HFD rats (P < 0.05). Supplementing each organic mineral, but particularly the combination of HFD + MgPic + ZnPic + SeMet reversed the responses with various degrees. None of the organic elements alone or as a combination of two exerted a prominent effect on parameters measured. Although not additive or synergistic, the combination of all organic minerals added to HFD (HFD + MgPic + ZnPic + SeMet) provided the greatest responses.
Keywords: Magnesium picolinate; Zinc picolinate; Selenomethionine; High-fat diet; Rat